One-step electrodeposited Co and Mn layered double hydroxides on Ni foam for high-performance aqueous asymmetric supercapacitors. (June 2022) - Emin, Adil; Song, Xiaoqiang; Du, Yihe; Chen, Yue; Yang, Mingzhe; Zou, Situo; Fu, Yujun; Li, Junshuai; Li, Yali; He, Deyan
Abstract: In this work, we report a high-performance and self-standing supercapacitor electrode composed of a Co and Mn layered double hydroxide (CoMn-LDH) nanostructure on Ni foam (NF) prepared by one-step electrochemical deposition. The CoMn-LDH electrode delivers a high capacitance of ~2673.6 F g −1 at 1 A g −1, with the excellent rate performance (~1488.0 F g −1 at 60 A g −1 ) and good cycle stability (~86.7% capacitance retention after 5000 cycles at 12 A g −1 ). The asymmetric supercapacitors assembled using the cathode of CoMn-LDH, the anode of activated carbon on carbon cloth and the electrolyte of 2.0 M KOH yield an energy density of ~97.5 W h kg −1 at 800.0 W kg −1, good cycling performance of ~89.2% capacitance retention after 5000 cycles at 5 A g −1 with the Columbic efficiency around 100%. These results indicate that the CoMn-LDH nanostructure on NF is a promising electrode for high-performance energy storage applications. Graphical abstract: The aqueous asymmetric supercapacitors with an energy density of up to 97.5 W h kg −1 at 800.0 W kg −1 is reported based on the cathode composed of one-step electrodeposited Co and Mn layered double hydroxides with an open and interconnected thin-layer-shaped nanostructure on nickel foam. Unlabelled Image Highlights: CoMn-LDHs were facilely grown on NF by one-step electrodeposition. High capacitance of 2673.6 F g −1 at 1 A g −1 and good rate capability were achieved. The assembled AASCs deliver 97.5 W h kg −1 at 800.0 W kg −1 and good stability.